Keragaman Genetik Gen NADH Dehydrogenase Subunit 6 pada Monyet Hantu (Tarsius Sp.) (GENETIC DIVERSITY STUDY ON NADH DEHYDROGENASE SUBUNIT 6 GENE OF TARSIUS SP.) - Widayanti, Rini; Susmiati, Trini; Artama, Wayan Tunas (Jurnal Veteriner, 2013)
In conservation, identification of tarsier species based on morphological and molecular characters isrequired. However, to date the identification of animals is simply based on their morphological characterand vocalizations, while in fact it is difficult to identify each species of Tarsius sp morphologicaly.  Thepurpose of this study is to obtain genetic markers that can be used to identify Tarsius sp on ND6 mitochondrialgenes and reveal affiliations and phylogenetic relationships Tarsius sp. with other members of primates.Samples were obtained from several original habitats of Tarsius sp. Three samples were taken from NorthSulawesi, one sample was collected from Central Sulawesi, three samples from Kalimantan  and threesamples from South Sumatra. The isolated DNA is then used as a template for amplification of DNAfragments by PCR. Amplicon (PCR product) obtained 566 bp and 629 bp. Nucleotide sequencing resultsshows 513 nucleotides, the smallest genetic distances of 0%, the highest of 30.2% and average of 16.3%.Nucleotide and amino acid sequences of ND6 can be used as genetic markers to differenciate T. spectrum,T. dianae and  T. bancanus but they fail to function as genetic markers to distinguish  T. bancanus ofKalimantan and Sumatra origin.
Keywords: Tarsius sp., sequencing, ND6 gene, nucleotides, mitochondrial DNA